Phytochemical Composition of Solanum retroflexum Analysed with the Aid of Ultra-Performance Liquid Chromatography Hyphenated to Quadrupole-Time-of-Flight Mass Spectrometry (UPLC-qTOF-MS) - Grace Daji; Paul Steenkamp; Ntakadzeni Madala; Bhekisisa Dlamini (Journal of Food Quality)
Solanum retroflexum (nightshade) is an edible plant that is consumed in some regions of South Africa. Its leaves are a good source of vitamins, proteins, and minerals. It appears that there is no scientific report about the phytochemical composition of S. retroflexum. Here, ultra-performance liquid chromatography coupled to quadruple-time-of-flight mass spectrometry (UPLC-qTOF-MS) technique was use to achieve an untargeted metabolite fingerprinting of this plant. A total of 30 phytochemicals, including alkaloids, flavonoids, and cinnamic acids derivatives, were identified from the methanolic leaf extracts. The concentration of solvent did not affect the type of compounds extracted. The extraction resulted in qualitative yields of molecules such as quercetin-3-rutinoside, kaempferol-3-0-rutinoside, kaempferol-3-0-glucoside, 3-caffeoylquinic acid, 5-caffeoylquinic acid, and 3, 4-di-caffeoylquinic acid. The present study confirms the presence of phytochemical compounds in S. retroflexum similar to other Solanum plants.